Farmer Participation on Sustainable Private Forest Management: Case of Cikeusal and Kananga Villages, Kuningan District PARTISIPASI PETANI DALAM PENGELOLAAN HUTAN RAKYAT LESTARI - Asep Sudrajat; Hardjanto .; Leti Sundawati (Jurnal Silvikultur Tropika, 2016)
Kuningan District is one of the largest private forest in West Java. Private forests of Cikeusal and Kananga Villages have certified by SVLK (verification of wood legality system) by 2013. Meanwhile, participation pattern on private forest under the SVLK certification has not been identified, hence it is important to know their performance in order to maintain and improve their forest. The aims of the research were : (1) to know the farmers participation pattern on private forest, (2) to analyze factors affected to the participation on sustainable private forest management, and (3) to analyze the impact of farmers participation on sustainability of private forest and farmer welfare. The research has conducted through survey approach. Data colection was conducted by sensus on 114 farmers, and the data analysis used qualitative descriptive method and pathway analysis. The result of this research showed that farmers participation were low, passive, and used a top down approach, either in Cikeusal or Kananga Villages. These participation generally were shaped by muscles and materials. It was conducted on entire private forest activities, including: planning, execution, and utilization phases. Internal and external factors, as well as farmer competence were significant factors to influence farmers participation on private forest management and sustainability of private forest. However there were not significant to influence farmer welfare.Key words : certification, farmer participation, Kuningan, private forest, welfare.